KEDUDUKAN SURAT EDARAN MENTERI KETENAGAKERJAAN TENTANG LARANGAN PENAHANAN IJAZAH DALAM HUKUM POSITIF INDONESIA - Utomo, Deny Setiyo (Jurnal Supremasi, 2025)
The Minister of Manpower issued Circular Letter Number M/5/HK.04.00/V/2025 as a response to the rampant practice of employers (companies) withholding workers' diplomas/personal documents. The research was conducted to identify and analyze the status and binding force of the Circular Letter of the Minister of Manpower within the Indonesian legal system. This research employs a normative legal research method with a statutory approach and a conceptual approach. The results of the study indicate that the Circular Letter is not classified as legislation or decisions. The Circular Letter is a policy rule issued based on the discretionary authority of the institution/government officials. The Circular Letter of the Minister of Manpower is only binding on the institutions/government officials addressed (Governors, Regency/City Heads, and other stakeholders). The Circular Letter of the Minister of Manpower cannot generally bind, thus, the circular letter serves as an announcement or notification for employers. The Circular Letter of the Minister of Manpower is issued as a legal correction regarding the withholding of diplomas that is not explicitly regulated in the Manpower Law. To strengthen the content of the Minister of Manpower's Circular Letter, it can be achieved by issuing a Ministerial Regulation or making amendments to the Manpower Law.